HUBUNGAN KEKUATAN OTOT LENGAN DAN PANJANG LENGAN DENGAN KEMAMPUAN LEMPAR CAKRAM SISWA KELAS XI IPS 1 SMA N 1 RAMBAH - Oktaria, Romi; Sinurat, Ridwan; Janiarli, Masdi (Journal Of Sport Education and Training, 2020)
This research was motivated by several problems that researchers encounter in the field, namely physical conditions and this technique was seen when students throw discs that are not far away, sometimes the throws also come out of the vector or trajectory lines.The purpose of this study was to determine whether there was a relationship between Arm Muscle Strength and Discus Throwing Ability of Students in Class XI IPS 1 of SMA Negeri 1 Rambah Arm Muscle Strength and Arm Length with Discus Ability Ability of Class XI IPS 1 Students of SMA Negeri 1 Rambah. This research is a type of correlational research with a total of 15 people and analyzed using product moment correlation. The results showed that: 1) There was a significant relationship between arm muscle strength and the ability to throw discs in class XI IPS 1 students in SMA Negeri 1 Rambah. With a value of Rcount (0.543)> Rtable (0.514), while Tcount (2.333)> Ttable (1,771). Thus, it can be concluded that the work hypothesis proposed by Ho was rejected and Ha was accepted, which means hypothesis one was accepted. 2) There was a significant relationship between the length of the arm with the ability to throw discs in class XI IPS 1 students of SMA Negeri 1 Rambah. With a value of Rcount (0.625)> Rtable (0.514), while Tcount (2.888)> Ttable (1,771). Thus, it can be concluded that the work hypothesis proposed by Ho was rejected and Ha was accepted, which means hypothesis two was accepted. 3) There was a significant relationship between Arm Muscle Strength and Arm Length with the Discus Throwing Ability of Class XI IPS 1 Students in SMA Negeri 1 Rambah. With a value of Rcount (0.709)> Rtable (0.514), it means that the joint strength of the Arm Muscles and Arm Length with the ability to Throw Discs in the same direction, with Fcount (2.72)> Ftable (2.48).